Aplicação da técnica de correlação de imagem para avaliação do fator de concentração de tensão - Caminha, Jessé Jêneses Oliveira (Universidade Federal Rural do Semi-Árido, 2019)
Engineering seeks to evolve its technologie each day to increase design safety. In the mechanics of materials field, the greatest concern is to build components in order to resist the applied forces. Mechanical constructions, are inevitably subjected to stress-concentrating effects, such as holes, notches, rips, among others. Based on this, studies on stress relieving agents, depending on the application position, have been developed with the purpose of extending the lifespan of mechanical constructions. The Digital Image Correlation (DIC) is an optical extensometry technique, innovative and very accurate, which allows strain measurement before a load and can be applied to verify levels of localized stress. The stress concentration factor is the ratio of the maximum and average stresses in the smallest cross section of an element, being a very relevant topic in mechanics, especially in projects that study localized loads in superficial discontinuities. The literature addresses several ways of determining the stress concentration factor, and the CID technique can present satisfactory results of stress values to determine this factor. With precise results, machine elements design evolve further, with the conviction of what might happen due to some unwanted loading, the most notable being the use of stress relievers at specific locations of the element. This work presents a study about the use of this optical method on the analysis of stress concentration factor in surface discontinuities of mechanical elements, having as general objective, to analyse the stress concentration factor on steel bars with high axial loads through the use of the CID technique and, as specific objectives: to revise the general literature describing the main definitions that allow to understand the mechanics of the solid and the Digital Image Correlation Technique; to characterize the procedures and equipment used for the method; to use MATLAB® software to crop highresolution camera images; to process the CorreliQ4® code, providing data for analysis and to compare the results obtained through the CID method with those of the used literature. Methodologically, the present study was carried out from experiments based on the CID method described in the literature, presenting as main results the possibility to determine displacement fields efficiently, accurately and quickly, despite having a higher cost due to the necessary equipment.
Monografia
Keywords: Correlação de imagem digital; Fator concentração de tensão; Aliviadores de tensão; Digital image correlation; Stress concentration factor; Stress relievers; ENGENHARIAS::ENGENHARIA MECANICA